Self-assessment of ESP oral performance: A tool for learning and fostering learner awareness. - Burkšaitienė, Nijolė (Journal of Education Culture and Society, 2020)
Aim. Research to date acknowledges the learning, instructional and assessment advantages of self-assessment used in different fields of study in higher education contexts, yet little known research has focused on its use for learning and raising learner awareness while studying English for Specific Purposes (ESP). To this end, the present small-scale study examines the use of self-assessment of philology students’ ESP oral performance at a university in Lithuania.Method. The data for this research was collected from undergraduate students’ written reports on their project presentations on the chosen ESP topics. To analyse the data, qualitative methodology of inductive content analysis was used.Results. The study resulted in the identification of five major dimensions covering problem areas in the students’ ESP oral performance. The findings indicate that self-assessment enabled the students not only to identify some gaps and difficulties in their ESP oral performance that call for action but also to establish the reasons which caused them, foresee how the gaps can be closed or the difficulties coped with. Furthermore, it allowed the students to make decisions that reached far beyond the self-assessment task. The results also demonstrate that self-assessment raised the students’ awareness of themselves as learners by giving them direction on how to perform better in the future.Conclusion. Self-assessment, as used in the present research, proves to be a valuable tool both for the students of ESP and their teachers as it reveals areas in the students’ performance that call for improvement, which enables ESP teachers to support their students to achieve better results in the future.